Creative Meaning-Making through a Multimodal, Interdisciplinary Exploration: Lessons for Higher Education Curriculum Enhancement. - Verster, Belinda; Collett, Karen; van den Berg, Carolien (Alternation)
Within the context of the neoliberal managerialism that is pervading higher education in South Africa, academia is driven by a stringent set of prescriptions. Teaching within this environment can constrain opportunities for creativity and lateral thinking by students and staff alike. Student protests in 2015 and 2016 provided a challenge and provocation to academics to think about the transformational nature of their curriculum design, content and pedagogy. This paper explores the collaboration between three senior academics as they engaged in a process of professional academic development. This experience opened up generative spaces for them to think in new and creative ways about their teaching and curriculum design. A collaborative autoethnographic methodology, informed by a social constructivist approach, was used to explore their experience. The authors trace their interactions with different mediums and each other as 'a continuous process of making and unmaking' (Jackson & Mazzei 2013: 262). The lenses of Touch (Barad 2012), an Ethic of Care (Tronto 2013) and Slow Pedagogy (Bozalek 2017) were used to make meaning of their experiences. Key lessons they identified as enhancing their teaching were: 'space of (for) becoming', 'academic praxis', 'deconstructing and reconstructing entanglement', 'learning-by-modelling', and 'decolonising thinking and meaning-making'. This paper holds lessons that can inform curriculum development in higher education, especially in a time when strong calls are mounting for 'disruptive shifts to revitalise higher education curricula' (Dhunpath & Amin 2019: 1).